Sirah Nabi Muhammad SAW dalam novel 'Dia': Karya Mohd Labib Ahmad - Nurhasma Muhamad Saad; Zulamali @ Abdul Aziz Matassan; Yuslina Mohamed; Wan Moharani Mohammad; Muhammad Marwan Ismail (NUN Gemilang Enterprise, 2024)
Vol. 5 No. 2 (2022): (Online Publication Date: 30 June 2022)